O Impact of Financial Education on the level of Financial Inclusion in Mozambique - Hilario Ramos, Ramos (Revista Interdisciplinar de Ciência Aplicada, 2023)
This article is about how financial education contributes to increasing financial inclusion in Mozambique, this is a literature review study, based on the financial inclusion plan of the Stock Exchange of Mozambique and the survey on Strengthening capacity and financial inclusion in Mozambique, so financial inclusion represents the level of coverage of such financial services to the population, while financial education represents a process of learning concepts and financial services available on the market that will provide and flexibility, enabling the proper use of money and help build a society with individuals with financial responsibility. We will verify in the three topics the development of financial education, financial inclusion and the level of financial inclusion in Mozambique, culminating with an analysis of the theoretical basis, making it possible to conclude that although there are other components also relevant to the effect, financial education contributes significantly to the level of financial inclusion in Mozambique.